Biotransformation of progesterone to hydroxysteroid derivatives by whole cells of Mucor racemosus - Mohamed, S. S.; El-Refai, A-M. H.; Sallam, LL. A. E-R.; Abo-Zied, K. M.; Hashem, A-G. M.; Ali, H. A. (Malaysian Journal of Microbiology, 2013)
Aims: The possibility of using Mucor racemosus cells in the biotransformation of progesterone to industrially important hydroxysteroid derivatives in one-step biotransformation process was investigated in this studyMethodology and results: The fungal strain was inoculated into the transformation medium which supplemented with PR as a substrate (5-50 mg). The transformation products were separated and characterized on the bases of their GC/MS analysis as 11α-hydroxyprogesterone (11α-HP) as main product (I); 4-pregnen-18-al-11β,21-diol-3,20-dione (Aldosterone) (II) and 20-hydroxy-pregnan-18-oic acid (III) as minor products. The organism was tested for PR bioconversion at different transformation periods (6-96 h), as well as optimization of the basal medium through the addition of different concentrations of yeast extract and peptone (0.5 to 4 g/L) at various pH values (4-9). The optimal biotransformation conditions for maximum production of these PR derivatives were observed using 0.2 g/L of PR, 3 g/L of yeast extract and 3 g/L peptone after 48 h at pH value 5.5. Under these optimal conditions, cells total bioconversion efficiency reached about 96% of the original added PR.Conclusion, significance and impact of study: Under these optimum conditions, M. racemosus has the ability to biotransform PR to 11α-HP (I), Aldosterone (II) and 20-hydroxy- pregnan-18-oic acid (III) with total bioconversion efficiency of 96 ± 1.77%. These results may be of industrial importance because compounds II and III had not been previously recorded as biotransformation products of PR.